2023
DOI: 10.12973/ijem.9.3.535
|View full text |Cite
|
Sign up to set email alerts
|

The Pedagogical Role of the Primary-School Headteacher: Insights From Greece

Nikolaos Alexopoulos,
Thomas Babalis,
Konstantina Tsoli
et al.

Abstract: <p style="text-align: justify;">The pedagogical and didactic guidance of teachers has been linked, in the relevant literature, to the school management’s adoption of the model of pedagogical leadership as well as to the assurance of a series of factors that influence it. This study aims at investigating the pedagogical role of the principal in Greek primary schools. Data were collected through an anonymous questionnaire completed by 133 Greek primary school head teachers. Results show that head teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
1
0
0
1
Order By: Relevance
“…In this regard, the research results showed that the models of transformational, pedagogical and distributed leadership (which, according to the literature, support PD and the presence of PLCs) exist in school units to a moderate degree. This finding is consistent with those of previous studies that assessed the power of pedagogical leadership (Alexopoulos et al, 2023) as well as distributed (Bestias & Balias, 2019) and transformational leadership (Eliophotou Menon, 2021;Mystakidou & Brinia, 2022) in ordinary public schools of the country. A possible interpretation for this could again be that, institutionally and practically, the principal's work in the country's schools is dominated by bureaucratic tasks.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, the research results showed that the models of transformational, pedagogical and distributed leadership (which, according to the literature, support PD and the presence of PLCs) exist in school units to a moderate degree. This finding is consistent with those of previous studies that assessed the power of pedagogical leadership (Alexopoulos et al, 2023) as well as distributed (Bestias & Balias, 2019) and transformational leadership (Eliophotou Menon, 2021;Mystakidou & Brinia, 2022) in ordinary public schools of the country. A possible interpretation for this could again be that, institutionally and practically, the principal's work in the country's schools is dominated by bureaucratic tasks.…”
Section: Discussionsupporting
confidence: 92%
“…Selain itu, hasil penelitian menunjukkan bahwa kepala sekolah menjalankan peran pedagogisnya dengan bekerja sama dan berkomunikasi terutama dengan anggota komunitas pendidikan sekolah. Temuan penting lainnya dari penelitian ini adalah bahwa faktor-faktor yang mendukung kepala sekolah dalam peran kepemimpinan pedagogis mereka, sulit ditemukan dalam realitas pendidikan hierarkis seperti di Yunani (Alexopoulos et al, 2023). Seperti halnya penelitian yang dilakukan oleh (Kurniawan, 2020), dalam penelitiannya bahwa berdasarkan analisis literatur ditemukan beberapa hal yang perlu ditekankan dalam proses perencanaan dan pelaksanaan pembelajaran yaitu, kesiapan bahan ajar, metode pembelajaran yang tepat, kenyamanan selama belajar, dan evaluasi hasil belajar dan perkembangan siswa.…”
Section: Pendahuluanunclassified